Oxford handbook of ophthalmology - Denniston, Alastair K. O.; Murray, Philip I. ([Oxford] : Oxford University Press, 2018)
This handbook offers a systematic summary of ophthalmic disease directed towards diagnosis, interim assessment and ongoing management. Now including an extensive online image bank the fourth edition provides rapid access to the information when it is needed, whether in the clinic, theatre or on the ward.
This edition previously issued in print: 2018.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 1, 2018).
Keywords: Ophthalmology; Eye -- Diseases